The reality of organizational silence among the leaders of governmental primary schools for boys in the city of Buraidah from the point of view of educational supervisors and teachers - Alshalash, Abulrahman Sulaiman (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the reality of organizational silence among primary school leaders in Buraidah from the point of view of educational supervisors and teachers. Using the descriptive analytical approach, the researcher used a questionnaire prepared by him as a tool for the study, which was applied to all educational supervisors in the city of Buraidah, whose number is (213) supervisors and primary teachers. At the level of dimensions, the school leader’s fear of feedback from the Education Department got the highest average (2.17), followed by the fear of feedback from teachers with an average of (1.99), and thirdly, the practice of abuse of official authority with an average of (1.82) and fourthly, the practice of means of communication with an average of (1.80). All of them are rated as (medium) practice. The study also revealed that the most important reasons for organizational silence are the lack of management support for the teachers’ proposals, the school leader’s fear of the education administration’s reactions, the lack of the school leader’s powers, the large number of responsibilities and tasks of the leader, and the lack of experience, and statistically significant differences were also found. Between the averages of the sample responses according to the job variable in favor of the educational supervisors, and according to the educational qualification variable in favor of the PhD holders, and based on the results, a number of recommendations and suggestions were presented. Among them: The school leader must provide sufficient participation opportunities for teachers to present their ideas. The school leader must not keep all powers for himself without delegating one of the work team.